This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
The given expression can be written as x 1 8 ( x 1 − 2 ) 1 6 + x 1 8 ( x 2 − 6 ) 8 By Vieta's Formula, x 1 + x 2 = 6 ⟹ x 2 = 6 − x 1 . Now putting the value of x 2 in the fraction and rewriting the equation, ( x 1 ( x 1 − 2 ) 2 ) 8 + ( x 1 − x 1 ) 8 = ( x 1 ( x 1 2 − 4 x 1 + 4 ) ) 8 + 1 = ( x 1 − 4 + x 1 4 ) 8 + 1 Now again by Vieta's Formula x 1 x 2 = 4 , ∴ The equation changes to ( x 1 + x 2 − 4 ) 8 + 1 = ( 6 − 4 ) 8 + 1 therefore final answer is 2 8 + 1 = 2 5 7